2013
DOI: 10.1186/1743-8977-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles: a review of current toxicological data

Abstract: Titanium dioxide (TiO2) nanoparticles (NPs) are manufactured worldwide in large quantities for use in a wide range of applications. TiO2 NPs possess different physicochemical properties compared to their fine particle (FP) analogs, which might alter their bioactivity. Most of the literature cited here has focused on the respiratory system, showing the importance of inhalation as the primary route for TiO2 NP exposure in the workplace. TiO2 NPs may translocate to systemic organs from the lung and gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
967
5
23

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,273 publications
(1,011 citation statements)
references
References 204 publications
(272 reference statements)
16
967
5
23
Order By: Relevance
“…Routes of exposure include the skin (e.g., sunscreens), the lungs (e.g., during painting), and the gastrointestinal tract (e.g., from processed foods, toothpaste, nutraceuticals, and pharmaceuticals) 1. Surgical titanium implants may also acquire oxide surfaces, which gradually wear releasing TiO 2 particles.…”
mentioning
confidence: 99%
“…Routes of exposure include the skin (e.g., sunscreens), the lungs (e.g., during painting), and the gastrointestinal tract (e.g., from processed foods, toothpaste, nutraceuticals, and pharmaceuticals) 1. Surgical titanium implants may also acquire oxide surfaces, which gradually wear releasing TiO 2 particles.…”
mentioning
confidence: 99%
“…There are studies about erythrosine as a photosensitizer for use in killing Staphylococcus aureus [5], Streptococcus mutans [6], and C. albicans [7,8] when activated by green light. Titanium dioxide is an oxide of titanium that has been widely used in industrial and consumer products [9], whose light-curing unit is blue LED wavelengths of 400-500 nm [10]. It has been widely used in the dental clinic to treat resin composite or glass ionomer.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have unequivocally shown that TiO2 exposure can migrate through different routes and accumulate in various organs (Chen et al, 2009;Shi et al, 2013;Jia et al, 2013), which, in turn cause oxidative stress, inflammation and apoptosis resulting in organ injury and failure. Dysfunction of the testes in turn affect reproduction and affects the function of the reproductive system (Jia et al, 2013).…”
Section: Ajptmentioning
confidence: 99%
“…Higher doses of TiO2 nanoparticles (324-2592 mg kg −1 bw) are accumulated in various organs as spleen, liver, kidney, lung and testes (Chen et al, 2009). Upon exposure to TiO2, pathological lesions occur in the liver, spleen, kidneys, testes and brain (Shi et al, 2013;Jia et al, 2013). Consequently disruption in organ function occur and alteration in inflammatory and defensive mechanisms of body.…”
Section: Introductionmentioning
confidence: 99%